Penerapan Paket Teknologi Pemupukan Organik-Anorganik Untuk Tanaman Cabai Merah di Lahan Kering Lombok Utara - Zaenal Arifin; Lolita Endang Susilowati; Mansur Ma’shum (Jurnal Gema Ngabdi, 2020)
Increased productivity of red chili plants is done to meet consumer demand which continues to increase by increasing cultivation techniques, one of which is fertilization. So far, farmers on dry land only rely on the use of high amounts of inorganic fertilizers. While the use of inorganic fertilizers continuously without being balanced with the provision of organic fertilizers can reduce the quality and fertility of the soil. This extention service aims to (1) provide understanding and enrich knowledge to farmers in the dry land of North Lombok regency to use a combination of organic and inorganic fertilizers in the cultivation of red chili, (2) practicing red chili cultivation techniques by giving a combination of organic and inorganic fertilizers. Community service was carried out within a period of six months to the "Tani Tulen" farmer group partners in Sambik Rindang hamlet, Salut village, Khayangan sub-district, North Lombok district. The approach method was used, participatory with the target empowerment process includes: (1) counseling; (2) the practice of planting red chilies with a combination of inorganic fertilizers. The results shows that (1) an increase in understanding farmers about the importance of using manure (compost) in increasing soil fertility, (2) the used of manure of 5 tons/ha combined with 350 kg Urea, 300 kg SP-36, and 200 kg KCl provide good growth in red chili plants.